Implementation of Character Education Policy on Student Learning Activities at Datokarama Palu State Islamic University - Sjakir Lobud; Muhammad Khairil; Nawawi Natsir (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to determine, analyze and reveal whether the character education policy can be implemented effectively at UIN Datokarama Palu. Qualitative research method. The research location is at Datokarama State Islamic University Palu. Informants as many as 7 people were selected purposively. Data collection was conducted using interview, observation and documentation techniques. The data analysis technique uses the Miles and Huberman interactive model. The theory that is used as a reference in this research is the theory of George C. Edward III (2010: 96-110) by looking at four factors of successful policy implementation, namely communication, resources, disposition, and bureaucratic structure. The results showed that only three factors were quite effective, namely communication, disposition, and bureaucratic structure. Meanwhile, the resource factor tends to be less effective because of the four resource elements studied, two elements are ineffective, namely the quantity of staff (human resources) is relatively minimal. Similarly, the facilities that are expected to support the successful implementation of character education policies are still not in accordance with the demands of the needs. The causal factors include the limited formation of new lecturer appointments and the natural disasters of the earthquake, tsunami and liquefaction that hit the Datokarama Palu State Islamic University Campus. Novelty in this research is that the implementation of character education policies is not only seen as the implementation of the main tasks of the implementers but also interpreted as a worship that can be a source of jariah charity.